The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1371/journal.pntd.0010242
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Chikungunya virus in bodily fluids: The INOVACHIK cohort study

Abstract: Background Chikungunya is a widely distributed, re-emerging tropical disease caused by the chikungunya virus (CHIKV). Little is known about the duration for which CHIK RNA are detectable in bodily fluids, especially genital secretions, and current evidence is based on small series or case reports. An understanding of viral dynamics across different body compartments can inform diagnostic testing algorithms and public health prevention interventions. Methodology A prospective cohort study was conducted to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…This finding was expected in serum samples, as Ct values in positive samples are inversely correlated with the viremia level, and CHIKV viremia declines over time [ 19 , 33 ]. However, a cohort study found the persistence of CHIKV RNA in the serum and saliva of patients for up to 60 days and in the urine for up to 95 days after the onset of the disease [ 29 ], indicating that molecular diagnosis may be attempted in samples collected during the post-acute phase of the illness. Because we tested only acute-phase samples, it was not possible to investigate the frequency of RT-qPCR positivity after the first week of symptom onset.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding was expected in serum samples, as Ct values in positive samples are inversely correlated with the viremia level, and CHIKV viremia declines over time [ 19 , 33 ]. However, a cohort study found the persistence of CHIKV RNA in the serum and saliva of patients for up to 60 days and in the urine for up to 95 days after the onset of the disease [ 29 ], indicating that molecular diagnosis may be attempted in samples collected during the post-acute phase of the illness. Because we tested only acute-phase samples, it was not possible to investigate the frequency of RT-qPCR positivity after the first week of symptom onset.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that CHIKV RNA can be detected in body fluids other than serum, such as saliva [ 26 , 28 , 29 ], urine [ 24 , 28 , 29 , 34 ], sperm [ 24 , 29 ], vaginal secretions [ 29 ], placenta or amniotic fluid [ 35 ], breast milk [ 36 ], synovial liquid [ 37 ] and cerebrospinal fluid [ 38 , 39 ]. Infectious CHIKV has also been detected in the saliva of mice, monkeys and humans [ 27 ], raising concerns about the potential for non-vector-borne transmission [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients provided blood samples for routine laboratory tests, including full blood cell count and biochemistry, along with specific tests: dengue NS1 antigen (Dengue NS1 AG Atrip, BIO RAD or Dengue Duo Test, BIOEASY) and dengue serology (Dengue IgM ELISA capture PANBIO, Dengue Indirect IgG ELISA, PAN BIO). After 2015, aliquots of blood and urine were also routinely used for dengue, zika and chikungunya virus detection, using real-time reverse transcriptase polymerase chain reaction assay (RT-PCR); and Chikungunya IgM and IgG antibody serology as described [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…To diagnose CHIKV infection, plasma and serum have become the most commonly used clinical samples [ 170 ]. However, other body fluids, such as saliva, urine, vaginal secretion, and semen can also contain CHIKV during the acute phase of the disease [ 171 ].…”
Section: Diagnosis Of Chikv Infectionmentioning
confidence: 99%